The Influence Of The Revolving Fund Program On Micro Business Development In Pematangsiantar City - Saragih, Jopinus; Tarigan, Adrian; Purba, Yeni Trisna; Zendrato, Ferawati (Jurnal Mamangan, 2024)
This study aims to determine the Effect Of Revolving Fund Program On Micro Business Development In Pematangsiantar City. In Indonesia, MSMEs have been proven to have an important role in overcoming the consequences and impacts of the economic crisis that occurred in 1997. Many large companies went bankrupt, while MSMEs were able to survive the crisis. The results of calculations using SPSS, the researcher concluded that consumer satisfaction of C'Betz Fried Chicken in Parepare City (Islamic Economic Analysis). This can be proven through the results of the t-test statistic obtained a sig. value of 0.00 <0.05. Thus, the comparison of t-count 5.611> t-table 2.001. so it can be concluded that H0 is rejected and Ha is accepted, which means that Price (X) has a positive and significant effect on consumer satisfaction (Y) of C'betz Fried Chicken in Parepare City (Islamic Economic Analysis). The results of calculations using SPSS, the researcher concluded that the price variable has a relationship (correlation). This can be seen in the sig. value of 0.00 < 0.05 so that it is stated that the two variables have a correlation (relationship). It can be seen in the Pearson Correlation value of 0.593 so that the relationship between the Price variable and the consumer satisfaction variable is quite strong.